PEMANFAATAN LAYANAN KOLEKSI ANAK, LANSIA DAN DISABILITAS DI PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA - Kota, Ignatius Januardi Wasa; Ginting, Richard Togaranta; Hidayatullah, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2025)
The National Library of the Republic of Indonesia as the main center and provider of information for users throughout Indonesia, provides a variety of special services to accommodate the information needs of its users. Some of the services provided by this library are collection services for children, the elderly and the disabled. This study aims to observe the utilization of collection services for children, the elderly and the disabled at the National Library of the Republic of Indonesia. This study used a descriptive qualitative method. Determining the source of key informant data using purposive sampling, in order to collect data using documentation, observation, literature study, interviews and using triangulation data collection techniques.This study shows the results that the use of children's, elderly and disabled collection services at the National Library of the Republic of Indonesia is optimal, seen by the use of children's collections which are in great demand, namely pop up books and story telling, while for the elderly the use of religious and health collections is also a means of recreationally and for the disabled, use collection services based on their disability condition, for the blind, use the braille book collection. Based on these results, it can be concluded that the collection services for children, the elderly and the disabled at the National Library of the Republic of Indonesia are optimal.